Productivity and convergence in European agriculture - Lajos Baráth; Imre Fertő (Hungarian Academy of Sciences, Institute of Economics, 2016)
In the paper we investigate relative productivity levels and decompose productivity change for European agriculture between 2004 and 2013. More specifically (1) we contribute to the debate whether agricultural Total Factor Productivity (TFP) has declined or not in the European Union (EU); (2) we compare the relative TFP level across EU member states and investigate the difference between 'old' member states (OMS, i.e. the EU-15) and 'new' member states (NMS) and (3) we test whether TFP is converging or not among member states. The empirical analysis applies the aggregate quantity framework developed in O'Donnell (2008), using country level panel data from the Economic Accounts for Agriculture for 23 EU member states. The results imply that TFP has slightly decreased in the EU over the analysed period; however there are significant differences in this respect between the OMS and NMS and across member states. Finally, our estimations support the productivity convergence hypothesis across the member states.
Keywords: Q12; 330; Total Factor Productivity (TFP) level; Agricultural productivity in the EU; Färe-Primont TFP index; TFP components; technical efficiency; scale efficiency; mix efficiency